Case‐Fatality Rate in Parkinson's Disease: A Nationwide Registry Study - Sipilä, Jussi O.T.; Kaasinen, Valtteri; Rautava, Päivi; Kytö, Ville (Movement disorders clinical practice (Hoboken, N.J.), 2024)
Background Patients with Parkinson's disease (PD) may have an increased risk of mortality, but robust estimates are lacking. Objective To compare mortality rates nationally between patients with PD and controls. Methods The case‐fatality rates of Finnish PD patients diagnosed in 2004–2018 (n = 23,688; 57% male, mean age at diagnosis = 71 years) and randomly selected sex‐ and age‐matched control subjects (n = 94,752) were compared using data from national registries. The median follow‐up duration was 5.8 years (max 17 years). Results The case‐fatality rate in patients with PD was higher than that in matched controls (HR 2.29; 95% CI 2.24–2.33; P < 0.0001). Excess fatality among PD patients was already present at 1 year from diagnosis and then plateaued at 29% at 12 years after diagnosis. The long‐term relative hazard of death in PD patients vs. matched controls did not differ based on sex. Patients with early‐onset PD (age at diagnosis <50 years old) had the highest relative hazard of death (HR 3.36) compared to matched control subjects, and the relative hazard decreased with higher age at diagnosis. The seven‐year excess risk of death decreased during the study period, especially in men. In patients with PD, male sex, increasing age, and increasing comorbidity burden were associated with an increased risk of death. Conclusions An increased risk of death among PD patients was evident from early on. The increase in risk was greatest among young‐onset patients. The excess risk in early PD declined during the study period, particularly in men. The reasons for this are unknown.